2005
DOI: 10.1007/s11060-004-2242-9
|View full text |Cite
|
Sign up to set email alerts
|

Focal paraneoplastic limbic encephalitis presenting as orgasmic epilepsy

Abstract: Orgasmic epilepsy is another mode of presentation of paraneoplastic limbic encephalitis leading to the diagnosis of an occult SCLC. EEG and MRI findings suggest that in this case the seizures originated from the left hemisphere. It is possible that early recognition and treatment of the SCLC will improve the prognosis of this neurologic entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 19 publications
2
23
0
1
Order By: Relevance
“…Our assumption is also consistent with Komisaruk et al's (2004) recent findings demonstrating an activation of the insula during online solo cervical-stimulation induced orgasm in spinalcord damaged women. In line with this, recent fMRI findings in men and EEG data in epileptic patients also showed that an orgasm results from a spread of neural activation within multiple brain areas, of which the insula might play a particular role Calleja et al, 1988;Chuang et al, 2004;Currier et al, 1971;Fadul et al, 2005;Freemon and Nevis, 1969;Janszky et al, 2002Janszky et al, , 2004McKenna, 2002;Ortigue and Bianchi-Demicheli, 2006;Shelley and Trimble, 2004). Along these lines, our results thus suggest that the insula serves as an integration cortex for multimodal and conceptual convergence of information that may play a role in second-order representations of bodily states (such as those involved in subjective quality ratings of orgasm) based on, for instance, recollections of sexual sensations, sexual fantasies and knowledge about sexual rewards or costs (sexual memory ;Spiering, 2004;Spiering et al, 2003).…”
Section: Discussionsupporting
confidence: 59%
“…Our assumption is also consistent with Komisaruk et al's (2004) recent findings demonstrating an activation of the insula during online solo cervical-stimulation induced orgasm in spinalcord damaged women. In line with this, recent fMRI findings in men and EEG data in epileptic patients also showed that an orgasm results from a spread of neural activation within multiple brain areas, of which the insula might play a particular role Calleja et al, 1988;Chuang et al, 2004;Currier et al, 1971;Fadul et al, 2005;Freemon and Nevis, 1969;Janszky et al, 2002Janszky et al, , 2004McKenna, 2002;Ortigue and Bianchi-Demicheli, 2006;Shelley and Trimble, 2004). Along these lines, our results thus suggest that the insula serves as an integration cortex for multimodal and conceptual convergence of information that may play a role in second-order representations of bodily states (such as those involved in subjective quality ratings of orgasm) based on, for instance, recollections of sexual sensations, sexual fantasies and knowledge about sexual rewards or costs (sexual memory ;Spiering, 2004;Spiering et al, 2003).…”
Section: Discussionsupporting
confidence: 59%
“…Although orgasm is not a pathological symptom of human sexual response, it can be assumed that epileptic orgasmic aura are caused by electric discharges at the same brain regions, which produce the physiological orgasm in healthy subjects. This assumption is reinforced by the fact that most of the present patients attributed their orgasmic aura to a feeling very similar to one which they experienced during sexual intercourse or masturbation (Bancaud et al, 1970;Calleja et al, 1988;Chuang et al, 2004;Crevenna et al, 2000;Erickson, 1945;Fadul et al, 2005;Freemon & Nevis, 1969;Gautier-Smith, 1980;Heath, 1972;Janszky et al, 2004;Janszky et al, 2002;Reading & Will, 1997;Remillard et al, 1983;Ruff, 1980;Torelli & Bosna, 1958).…”
Section: Neurological Case Reportsmentioning
confidence: 56%
“…For a better understanding of this phenomenon, we focused our review on female patients who experienced spontaneous orgasms (Bancaud et al, 1970;Calleja, Carpizo, & Berciano, 1988;Chuang, Lin, Lui, Chen, & Chang, 2004;Crevenna, Homann, Feichtinger, Ott, & Korner, 2000;Currier, Little, Suess, & Andy, 1971;Erickson, 1945;Fadul, Stommel, Dragnev, Eskey, & Dalmau, 2005;Freemon & Nevis, 1969;GautierSmith, 1980;Heath, 1972;Janszky et al, 2002Janszky et al, , 2004Reading & Will, 1997;Remillard et al, 1983;Ruff, 1980;Torelli & Bosna, 1958; Table 1). This approach allowed us to find 20 patients, aged 20-57 years, who experienced spontaneous orgasms subsequent to the recruitment of specific brain areas.…”
Section: Neurological Case Reportsmentioning
confidence: 99%
“…These antibodies were characterized by the staining of the nuclei of Purkinje and granular cells of the cerebellar neurons and of the myenteric plexus but negative reactions of anti-nuclear antibodies on the liver sections. The specificity of this reaction was further confirmed by Western immunoblotting All cases but one (''orgasmic epilepsy'' [7]) had clinically documented epileptic phenotypes: left facial twitching [3,4] right facial twitching, [5] right arm jerking, [6] left hand (case 1), [3] and right face and hand (case 2). on Purkinje and granular cell extracts of cerebellum, demonstrating a 35-40 kD band.…”
Section: Case Reportmentioning
confidence: 82%